A Critical Review Study on the Effect of Distributive Justice and Procedural Justice on Organizational Commitment and Satisfaction - Ardian Mustofa (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research is a review of the article by Heru Kurnianto Tjahjono, Olivia Fachrunnisa, & Majang Palupi which was published in the International Journal of Business Excellence in January 2019, 17(3): 336-360 with the title Configuration of Organizational Justice and Social Capital: Their Impact on Satisfaction and Commitment. The purpose of this study is to analyze whether social capital modifies the impact of organizational equity on individual satisfaction and organizational commitment. The purpose of this study was to determine whether social capital has a moderating effect on the relationship between organizational justice and individual satisfaction and organizational commitment. In addition, this study examines whether individual satisfaction and organizational commitment are influenced by contextual differences or interactional learning models. The findings suggest that it is important to consider the moderating role of social capital in the relationship between distributive and procedural justice, as well as satisfaction with individual and organizational commitment. We can conclude theoretically from the experimental design that distributive and procedural justice have a disproportionate impact on individual satisfaction and commitment. In elaborating individual satisfaction, distributive justice dominates procedural justice. Procedural justice, on the other hand, is more important in building organizational commitment.